The Effect of Service Quality, Customer Value and Corporate Image on Customers’ Satisfaction (Study on Customer of PT. Pos Indonesia (Persero) Malang Branch) - Alhaq, SE, Faizal M.; Rohman, SE, Msi, Dr.Fatchur; Isharina, SE., MM, Ikhtiara Kaideni (Jurnal Ilmiah Mahasiswa FEB, 2012)
The purpose of this research is to examine the effect of Service Quality, Customer Value, and Corporate Image on Customer Satisfaction at PT. Pos Indonesia (Persero) branch Malang. In order to know the relationship occur among the independent variables (Service Quality, Customer Value and Corporate Image) on Customer Satisfaction the regression analysis, F test and t test was conducted. This research is explanatory research, in accordance with its purpose to explain the correlation and relations of some fixed variables. The  samples in this research were  the customers of PT. Pos Indonesia (Persero) branch Malang. The sampling technique is Purposive sampling and the research instruments tested using the validity test, reliability test and classical assumption test. The hypothesis testing was using the F and t test to analyze the data to be used in Multiple Regression Analysis. The multiple regressions showed that, simultaneously, Service Quality, Customer Value and Corporate Image are significant affect on PT. Pos Indonesia (Persero) branch Malang. So does  partially tested, the variables of Service Quality, Service Value and Corporate Image are significant affect on  customer satisfaction. While  dominant test shows corporate image has dominant affect on customer satisfaction. Keywords: customer satisfaction, service quality, service value, corporate image.